Implementation of smart agrologistics for strengthening economic resilience of steamed fish enterprises in Erorejo Wadaslintang - Rindra Yusianto; Iswoyo; Amalia; Herwin Suprijono (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Steamed fish represents one of the primary processed fish products produced by fishermen in Wadaslintang. In the aftermath of the COVID-19 pandemic, the Wadaslintang Fish Craftsmen and Management KWT Rahayu faced various obstacles, particularly in securing adequate supplies of red tilapia (Oreochromis sp.) as raw material and in expanding their marketing reach. This service program aims to implement smart spatial agrologistics to increase production capacity, expand market reach, and strengthen the economic resilience of steamed fish enterprises in Erorejo Wadaslintang. Over eight months, the program targeted 15 KUB members and applied several participatory approaches, including interviews, data segregation, and georeferenced digitization, to identify reliable raw material suppliers, map potential markets, and define marketing coverage. The initiative demonstrated that green spatial agrological innovation could be successfully adapted to strengthen local fishing enterprises. As a direct outcome, membership of steamed fish businesses increased from 15 to 20 participants, while marketing areas expanded to Lampung and Banjarmasin. Furthermore, production capacity rose significantly from 60 kilograms per day to 150 kilograms per day. These results confirm that the adoption of innovative spatial-based agrological technology can enhance productivity, improve resource management, and boost the economic resilience of fishing communities in Wadaslintang.